Удосконалення правового регулювання у сфері діяльності політичних партій на сучасному етапі - Сон Софія Сергіївна; Сон София Сергеевна; Son Sofija (My University, 2014)
The practice of political parties in Ukraine and development of appropriate legislation require continuous improvement mechanism of legal regulation in this area in order to meet the relevant law as the Constitution of Ukraine and other laws to prevent the emergence of conflicts of law.
Сон С. Удосконалення правового регулювання у сфері діяльності політичних партій на сучасному етапі / С. Сон // Юридичний вісник. - 2014. - № 4. - С. 50-53.
Keywords: політичні партії; правові колізії; законодавство про політичні партії; удосконалення правового регулювання; політична система; политические партии; правовые коллизии; законодательство про политические партии; усовершенствование правового регулирования; политическая система; political parties; legal conflicts; law about political parties; improvement of legal regulation; political system